2016
DOI: 10.13189/ujer.2016.041008
|View full text |Cite
|
Sign up to set email alerts
|

Students' Involvement in Decision Making and Their Academic Performance in Embu West Sub-County of Kenya

Abstract: Although studies have shown that involving students in decisions that impact their educational outcomes may improve their academic performance, little effort has been put in collating students' views on the appropriate extent of such involvement. Students are key stakeholders and beneficiaries of educational outcomes, as well as determinants of examination results. It is therefore important to study the impact of their inclusion into the school key decision systems. Using data from twelve public day secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…According to Mati, Gatumu, and Chandi [31], the participation of students in the key decisions of their educational process increases their motivation towards school tasks, as well as their sense of belonging; therefore, there is a greater inclination to comply with established rules, which affects their academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mati, Gatumu, and Chandi [31], the participation of students in the key decisions of their educational process increases their motivation towards school tasks, as well as their sense of belonging; therefore, there is a greater inclination to comply with established rules, which affects their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have already revealed the influence of self-awareness [29], selfreflection [30], and decision-making [31] in academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…(Fang et. al., 2013) Furthermore, it was found that students involvement in the key decisions of their educational process produces motivation, a sense of ownership and therefore a higher inclination to abide by the set rules, personal drive to meet the individual and collective goals, and an overall higher academic performance (Mati et. al., 2016)…”
Section: Significant Effect Of Components and Characteristics Of The ...mentioning
confidence: 99%
“…This helps them to grow and develop into responsible adults. Mati et al (2016) promoted that student participation in disciplinary issues helps them grow responsibly and accept the consequences of their own decisions and actions. In his study, Hannam (2001) found that participative activities in both public and private schools improved school attendance, students' self-esteem, motivation, and attainment among the students.…”
Section: Review Of Related Literaturementioning
confidence: 99%